The Internet Diabetes Self-Management Workshop for American Indians and Alaska Natives - Jernigan, Valarie Blue Bird (Health Promot Pract, 2010)
Type 2 diabetes disproportionately affects American Indians and Alaska Natives (AI/ANs). In the larger population, patient self-management has become an increasing focus of the health care system to help reduce the impact of diabetes. However, little is known about patient self-management programs designed for AI/ANs. This study reports on the feasibility of implementing the Stanford Internet Diabetes Self-Management Workshop within the AI/AN population using a participatory research approach. This is a continuation of self-management studies to assist in meeting the needs of both patients and the health care system for health services that are effective (evidence based), efficient, and culturally appropriate. To our knowledge, this is the first study examining the effectiveness of an Internet-based diabetes patient self-management program among AI/ANs. This article reports on a pilot for a larger randomized study that is ongoing.